CoFe-coated NBC composite catalyst as well as preparation method and application thereof
By loading Co and Fe on nitrogen-doped biochar, the CoFe@NBC composite catalyst is prepared, and the PMS is activated to degrade bisphenol S, which solves the problems of low efficiency in removing bisphenol S and secondary pollution caused by metal ion leaching in the prior art. Efficient and stable water pollution treatment has been achieved.
Patent Information
- Application Number
- CN202411358394.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art cannot effectively remove bisphenol S (BPS) in water, and the commonly used adsorption methods and biological treatment methods are inefficient, which has the problem of secondary pollution caused by metal ion leaching.
Develop a CoFe@NBC composite catalyst, prepared by supporting Co and Fe on nitrogen-doped biochar (NBC), using hydrothermal reaction and calcining processes, forming a catalyst with a high specific surface area and porous structure, activates the persulfate salt (PMS) Degrades bisphenol S.
The removal rate of bisphenol S is greater than 99.99%, reducing the leaching of metal ions, improving the stability and reusability of the catalyst, reducing the cost of raw materials, and having good structural stability and efficient pollutant degradation. ability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst synthesis, and in particular to a CoFe@NBC composite catalyst and a preparation method and application thereof. Background Art
[0002] Sulfate radical-based advanced oxidation processes (SR-AOPs) are considered to be an effective method for degrading organic pollutants. - ) can be activated by energy (heat, light radiation and ultrasound), chemicals (acids, alkalis, phenols, etc.) and carbon materials (carbon nanotubes, carbon fibers and graphene).
[0003] Biochar (BC) is a green material made by carbonizing biomass under a limited oxygen environment. It has a large specific surface area, rich functional groups and is easily available. However, the catalytic performance of raw biochar is poor and cannot meet the requirements of complex water pollution treatment. Heteroatom doping (N, S, P, etc.) can adjust the electronic state and active sites of carbon materials and improve catalytic activity. N atoms have higher electronegativity than C atoms, and electrons will flow from C atoms to N atoms, which is conducive to the adsorption of PMS. At the same time, it can also promote the generation of active species and the degradation of pollutants, but the catalytic effect is not as good as that of transition metal catalysts.
[0004] Transition metals exhibit good catalytic performance due to their variable valence states. With the deepening of research on transition metal activation and the similar properties of transition metals, people are increasingly inclined to bimetallic activation (Fe / Co, Co / Mn, Co / Cu, etc.), so that they have more sites for activation and sites, thereby more efficiently activating PMS. However, in practical applications, secondary pollution caused by metal ion leaching must be avoided. Therefore, researchers are committed to developing composite catalysts. Heterogeneous transition metal-based nitrogen-doped carbonaceous materials have received widespread attention because the nitrogen-doped carbon matrix can effectively prevent the aggregation of nanoparticles and is more conducive to preventing the leaching of metal ions. At the same time, the co-modification of carbon-based materials using the synergistic effect between metal and non-metal elements can significantly improve the activation performance of carbon-based catalysts for PMS.
[0005] Due to strict regulation on the use of bisphenol A, bisphenol S (BPS4,40-sulfonyldiphenol) is used as a safe alternative to it and is widely used in the manufacture of polycarbonate, thermal recording materials (color developers) and surfactants. At the same time, it is also used as an additive in the production of pesticides, leather tanning agents and resin flame retardants. BPS has a certain disruptive effect on the human endocrine system, has strong thermal stability and light stability, is persistent, and has serious hazards to humans and organisms. BPS is often detected in water environments and can also be detected in human urine and breast milk serum. However, the commonly used adsorption method and biological treatment method cannot effectively remove bisphenol S.
[0006] Therefore, the present invention proposes a CoFe@NBC composite catalyst and a preparation method thereof, and the application of the catalyst in activating peroxymonosulfate to degrade bisphenol S (BPS) is of great significance. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a CoFe@NBC composite catalyst and a preparation method and application thereof. The CoFe@NBC composite catalyst prepared by the present invention has a high specific surface area, rich pore structure and a large number of active sites, which is beneficial to the activation of PMS and the degradation of pollutants.
[0008] To achieve the above object, the technical solution of the present invention is as follows: The present invention provides a method for preparing a CoFe@NBC composite catalyst, comprising the following steps: 1) First, the collected wheat straw is pre-treated, and after the pre-treatment, wheat straw biomass powder is obtained for standby use; 2) The wheat straw biomass powder obtained in step 1) and Co(NO3)2·6H2O and Fe(NO3)3·9H2O are dissolved in water, and then isopropanol and ammonia water are added and stirred evenly, and then the solution is transferred to an autoclave for hydrothermal reaction. After the hydrothermal reaction, a CoFe@NBC precursor is obtained; 3) The CoFe@NBC precursor obtained in step 2) is placed in a tubular furnace in a N2 atmosphere for calcination. After the calcination is completed, the material is cooled to room temperature and then taken out for grinding to obtain a CoFe@NBC composite catalyst.
[0009] Furthermore, the specific process of pre-treating the collected wheat straw in step 1) is as follows: The collected wheat straw is repeatedly washed with water to remove dead leaves and dust on the surface, then placed in a drying oven at 105°C for 30 min, and then transferred to 60-80°C for drying. Finally, the dried wheat straw is crushed using a plant crusher to complete the pretreatment of the wheat straw biomass.
[0010] Furthermore, in step 2), the mass ratio of wheat straw biomass powder to Co(NO3)2·6H2O and Fe(NO3)3·9H2O is 1:0.29-0.87:0.81-1.62; and the mass fraction of ammonia water in the mixed solution is 44.69-51.86%.
[0011] Furthermore, in step 2), the volume ratio of isopropanol to aqueous ammonia is 1:0.71-2.86.
[0012] Furthermore, in step 2), the hydrothermal reaction temperature is 175-185° C., and the reaction time is 12-13 h.
[0013] Furthermore, in step 3), the calcination temperature is 780-820° C. and the calcination time is 3-4 h.
[0014] The invention provides a CoFe@NBC composite catalyst prepared by the method.
[0015] The present invention also proposes an application of the CoFe@NBC composite catalyst in activating peroxymonosulfate to degrade bisphenol S.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The catalyst of the present invention is a catalyst that loads bimetallic Co and Fe on NBC, so that the CoFe@NBC composite catalyst has a high specific surface area and a large number of active sites, which is beneficial to the activation of PMS and the degradation of pollutants; the CoFe@NBC composite catalyst prepared by the present invention is used to activate peroxymonosulfate (PMS) to degrade bisphenol S. After reaching adsorption equilibrium, after reacting with PMS for 60 minutes, the removal rate of bisphenol S in the solution is greater than 99.99%; 2) The N-doped biochar (NBC) of the present invention exhibits a porous structure with a high specific surface area, which can provide a large number of sites for the loading of bimetallic Co and Fe, reduce the aggregation of active sites, and make the Co and Fe substances more evenly distributed on its surface; at the same time, NBC contains abundant N atoms, among which graphite N and pyridine N can destroy the inertness of the sp2 carbon layer or change its valence band to increase the catalytic activity; NBC can also prevent the leaching of metal ions; in addition, the N-doped biochar has good structural stability, so that the catalyst has long-term catalytic activity; the CoFe@NBC composite catalyst prepared by the present invention has low raw material cost, simple preparation process, and strong practicality; 3) The CoFe@NBC composite catalyst prepared by the present invention has certain magnetism, is easy to recycle, and has good stability and reusability. After multiple catalytic activation PMS experiments, it still has high catalytic activity; 4) The catalyst prepared by the present invention solves the secondary pollution caused by the difficulty in recycling the homogeneous activator. At the same time, using biochar as a carbon-based material can achieve the purpose of resource utilization and has a high efficiency in pollutant degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a process diagram of the catalyst preparation process of the present invention; Figure 2 SEM images of different catalytic materials; Among them, 2 (a) is the SEM image of the original biochar (BC); 2 (b) is the SEM image of the N-doped biochar (NBC); 2 (c) is the SEM image of the Co and Fe bimetallic doped biochar (CoFe@BC); 2 (d) is the SEM image of the bimetallic loaded nitrogen-doped biochar (CoFe@NBC); Figure 3 Raman spectra of different catalytic materials; Figure 4 N2 adsorption-desorption isotherms of different catalytic materials; Figure 5 is the pore size distribution curve of different materials; Figure 6 FT-IR images of different materials; Figure 7 (a) Full XPS spectra of the four materials; Among them, 7 (b), 7 (c), 7 (d), 7 (e) and 7 (f) are high-resolution scans of C1s, O1s, N1s, Fe2p and Co2p of CoFe@NBC, respectively; Figure 8 is the hysteresis regression curve of CoFe@NBC; Fig. 9 The adsorption diagram of different materials on BPS; Fig.10 It is the degradation diagram of BPS under different systems; Fig.11 This is the effect diagram of different pH on BPS degradation; Fig.12 This is a diagram showing the effect of different catalyst dosages on BPS degradation; Fig.13 This is a graph showing the effect of PMS dosage on BPS degradation. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with embodiments and drawings, but the scope of protection of the present invention is not limited to the described scope. Example 1
[0019] The collected wheat straw was washed with water, fixed in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After drying, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder, 1.0 mmol Co(NO3)2·6H2O and 1.5 mmol Fe(NO3)3·9H2O were added to 10 mL of water, and then 7 mL of isopropanol and 15 mL of ammonia water were added and stirred for 30 min. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C in a N2 atmosphere for constant temperature calcination for 3 h, cooled and ground to obtain a CoFe@NBC composite catalyst. Example 2
[0020] The collected wheat straw was washed with water, fixed in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After drying, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder, 1.0 mmol Co(NO3)2·6H2O and 1.5 mmol Fe(NO3)3·9H2O were added to 10 mL of water, and then 7 mL of isopropanol and 15 mL of ammonia water were added and stirred for 30 min. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 900°C for constant temperature calcination for 3 h under a N2 atmosphere, and then cooled and ground to obtain a CoFe@NBC composite catalyst. Example 3
[0021] The collected wheat straw was washed with water, withered in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After it was dried, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder, 1.0 mmol Co(NO3)2·6H2O and 1.5 mmol Fe(NO3)3·9H2O were added to 10 mL of water, and then 7 mL of isopropanol and 20 mL of ammonia water were added and stirred for 30 min. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C in a N2 atmosphere for constant temperature calcination for 3 h, cooled and ground to obtain a CoFe@NBC composite catalyst. Example 4
[0022] The collected wheat straw was washed with water, withered in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After it was dried, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder and 1.0 mmol Co(NO3)2·6H2O and 2.0 mmol Fe(NO3)3·9H2O were taken, and then 7 mL of isopropanol and 15 mL of ammonia water were added and stirred for 30 min. Then the solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C for constant temperature calcination for 3 h under N2 atmosphere, and then cooled and ground to obtain a CoFe@NBC composite catalyst. Example 5
[0023] The collected wheat straw was washed with water, sterilized in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After it was dried, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder and 1.5 mmol of Co(NO3)2·6H2O and 1.5 mmol of Fe(NO3)3·9H2O were taken in 10 mL of water, and then 7 mL of isopropanol and 15 mL of ammonia water were added and stirred for 30 min. Then the solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C for constant temperature calcination for 3 h under N2 atmosphere, and then cooled and ground to obtain a CoFe@NBC composite catalyst.
[0024] Comparative Example 1 The collected wheat straw was washed with water, fixed in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After drying, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder, 1.0 mmol Co(NO3)2·6H2O and 1.5 mmol Fe(NO3)3·9H2O were added to 10 mL of water, and then 7 mL of isopropanol and 0 mL of ammonia water were added and stirred for 30 min. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C for constant temperature calcination for 3 h under a N2 atmosphere, and then cooled and ground to obtain a CoFe@BC composite catalyst.
[0025] Comparative Example 2 The collected wheat straw was washed with water, withered in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C to dry to constant weight. After it was dried, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder was added to 10 mL of water, and then 7 mL of isopropanol and 15 mL of ammonia water were added and stirred for 30 min, and then the solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 180°C for 12 h. After the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C in a N2 atmosphere for constant temperature calcination for 3 h, and then cooled and ground to obtain an NBC composite catalyst.
[0026] Comparative Example 3 The collected wheat straw was washed with water, withered in a drying oven at 105°C for 30 min, and then transferred to a constant temperature drying oven at 60°C for drying to constant weight. After drying, it was crushed with a plant crusher and passed through a 100-mesh sieve to obtain wheat straw biomass powder; 0.5 g of wheat straw biomass powder was heated to react at 180°C for 12 h, and after the reaction, centrifugation, washing and drying were completed to prepare a precursor; the precursor was placed in a tubular furnace and heated to 800°C under a N2 atmosphere and calcined at a constant temperature for 3 h, and then cooled and ground to obtain a BC composite catalyst.
[0027] The catalysts prepared in Example 1 and Comparative Examples 1-3 were analyzed as follows: like Figure 2 As shown in (a), the SEM image of the original biochar (BC) shows a typical fibrovascular structure; Figure 2 As shown in (b), the morphology of N-doped biochar (NBC) changes significantly and becomes porous, which is mainly caused by the corrosion of ammonia water.
[0028] like Figure 2 As shown in (c), Co and Fe bimetallic doped biochar (CoFe@BC), some particles can be observed on its surface.
[0029] like Figure 2 (d) shows the SEM image of bimetallic loaded nitrogen-doped biochar (CoFe@NBC), which exhibits a rough porous honeycomb structure with some particles observed on its surface, indicating that the Co and Fe bimetallics are successfully doped; the co-doping of N, Co, and Fe enriches the void distribution on the biochar surface.
[0030] like Figure 3 As shown, the I of the original biochar (BC) D / I G The intensity is the smallest, indicating that the higher the degree of graphitization, it is worth noting that the I D / I G The intensity is greater than that of BC, and the higher the degree of defects, indicating that the doping of N, Co, and Fe atoms enriches the defect structure of BC.
[0031] like Figure 4 It can be seen that all materials exhibit type IV isotherms and form hysteresis loops of different amplitudes at P / P0>0.4, indicating that they all have rich mesoporous structures.
[0032] from Figure 5 It can be observed that all materials have sharp peaks at 2~5nm, indicating that the hierarchical porous structure of the samples is between mesopores and micropores.
[0033] like Figure 6 As shown in the figure, all catalysts contain similar active groups; for CoFe@NBC, 3421cm -1 The absorption peak at 1630cm is mainly due to the stretching vibration of the -OH functional group; -1 The energy band at 1064cm is attributed to HOH vibration or C=O stretching; -1 The peak at 604 cm is attributed to the COC stretching vibration of carbon materials; -1 The peak at is due to the Metal-O bond.
[0034] By comparing the full spectrum Figure 7(a) It can be seen that N, Co, and Fe are successfully doped into the original biochar (BC) to form CoFe@NBC; in the fine spectrum of C1s of CoFe@NBC (b), the peaks with binding energies of 284.8, 285.9, and 288.5 eV correspond to the functional groups CC / C=C, CN, and CO, respectively. In the spectrum of O1s (c), the peaks with binding energies of 530.8, 532.1, and 533.6 eV belong to the oxygen-containing functional groups O=C, OC, and OC=O, respectively. In the high-resolution scan of N1s (d), the peaks at 397.9, 399.8, and 401.3 eV correspond to pyridinic N, pyrrolic N, and graphitic N, respectively. In Fe2p (e), it can be seen that the peak at 710.3 eV belongs to Fe 2+ (2p 3 / 2 ), the peak at 723.9 eV belongs to Fe 2+ (2p 1 / 2 ). The peak at 712.7 eV belongs to Fe 3+ (2p 3 / 2 ), the peak at 725.6 eV belongs to Fe 3+ (2p 1 / 2 ). The peak at 718.2 eV is a satellite peak of Fe2p. 0 The peaks are located at 707.2 eV and 719.2 eV. Figure (f) is a high-resolution scan of Co2p. The peaks at 779.4 and 794.9 eV are Co 3+ (2p 3 / 2 ) and Co 3+ (2p 1 / 2 ). 2+ (2p 3 / 2 ) and Co 2+ (2p 1 / 2 ) peaks correspond to 782.1 and 796.6 eV, respectively. The peaks at 786.0 and 803.2 eV are Co2p 3 / 2 and Co2p 1 / 2 The satellite peaks of 0 characteristic peaks.
[0035] like Figure 8 As shown, by observing the magnetic hysteresis regression curve (VSM), it can be seen that the saturation magnetization intensity (Ms) value is 56.7emu / g, which can achieve the goal of magnetic separation. This shows that at least after the reaction, a certain external magnetic field can effectively separate the catalyst.
[0036] The BET analysis of BC, NBC, CoFe@BC and CoFe@NBC is as follows: Table 1 BET analysis of four materials
[0037] By comparing Table 1, it can be clearly found that the co-doping of N, Co, and Fe greatly increases the specific surface area of biochar, from 152.17 m 2 ·g -1 Increased to 817.66 m 2 ·g -1 . It can expose more active sites, thereby improving the adsorption and catalytic performance.
[0038] Embodiment 6-9 100 mL of 50 mg / L bisphenol S (BPS) solution was added to four identical 250 mL beakers, and then 0.05 g of different types of catalysts (BC, NBC, FeCo@BC, CoFe@NBC) were added thereto, and then the adsorption experiment was started under magnetic stirring at 500 rpm.
[0039] like Fig. 9 As shown in the figure, all materials can reach adsorption equilibrium within 30 minutes. Among them, CoFe@NBC has a good adsorption effect on BPS, and can remove about 50% of BPS within 30 minutes. This may be because the doping of Co and Fe bimetallic and N doping greatly increase its specific surface area and void structure, providing more adsorption sites; at the same time, metal ions can form complexes with pollutants. The adsorption efficiency is improved through ion exchange and complexation.
[0040] Examples 10-13 100 mL of 50 mg / L bisphenol S (BPS) solution was added to four identical 250 mL beakers, one of which was free of catalyst and the remaining four were added with 0.05 g of different types of catalysts (BC, NBC, FeCo-BC, CoFe@NBC). Then, after magnetic stirring at 500 rpm for 30 min, 1 mM PMS was added under stirring to carry out the degradation experiment of BPS.
[0041] like Fig.10 As shown in the figure, when PMS was added alone, BPS decreased slightly; when PMS and FeCo-NBC were added at the same time, it was found that BPS could be completely degraded within 60 min, which shows that CoFe@NBC can effectively activate PMS, thereby efficiently catalyzing PMS to degrade BPS.
[0042] Examples 14-18 In five identical 250 mL beakers, 100 mL of bisphenol S (BPS) solution with a concentration of 50 mg / L was added, and 0.05 g of CoFe@NBC composite catalyst was added thereto. The pH was adjusted to 3, 4, 8, 11 and the pH value of the natural system was 5.84 for comparative experiments to explore the effect of pH on the catalytic effect.
[0043] like Fig.11 As shown in the figure, except when the pH is 11, the degradation effect is poor, and the removal rate is still relatively high (>90%) under other pH conditions. It can be considered that CoFe@NBC can effectively degrade BPS in a wide pH range, and the degradation effect is even better under weak acid, weak base and neutral conditions.
[0044] Examples 19-22 100 mL of 50 mg / L bisphenol S (BPS) solution was added to four identical 250 mL beakers, and then 0.025 g, 0.05 g, 0.075 g, and 0.100 g of CoFe@NBC composite catalyst were added thereto, respectively. After magnetic stirring at 500 rpm for 30 min, 1 mM PMS was added under stirring to carry out the degradation experiment of BPS.
[0045] like Fig.12 As shown in the figure, in the system without CoFe@NBC, only PMS acts on BPS alone, and the degradation is very small. In the reaction system with low catalyst concentration, the removal rate of BPS within 60 minutes is less than 90%. When the CoFe@NBC concentration reaches 0.5g / L, the degradation rate reaches 100% within 60 minutes. Further increasing the catalyst concentration does not significantly improve the degradation efficiency.
[0046] Examples 23-26 In a 250 mL beaker, 100 mL of bisphenol S (BPS) solution with a concentration of 50 mg / L was added, and then 0.05 g of CoFe@NBC composite catalyst was added thereto. After magnetic stirring at 500 rpm for 30 min, 0.5, 1.0, 1.5, and 2.0 mM PMS were added under stirring conditions for degradation experiments.
[0047] The experimental results are as follows Fig.13 As shown in the figure, the removal of BPS in the system without adding PMS is only the adsorption of CoFe@NBC. When the PMS concentration is 0.5mM, the removal rate of BPS is about 80% within 60min; when it is increased to 1mM and 1.5mM, BPS can be completely removed within 60min; when the PMS concentration increases to 2mM, the removal rate reaches 100% within 60min.
Claims
1. A method for preparing a CoFe@NBC composite catalyst, characterized in that The steps include: 1) First, the collected wheat straw is pre-treated, and after the pre-treatment, wheat straw biomass powder is obtained for standby use; 2) The wheat straw biomass powder obtained in step 1) and Co(NO3)2·6H2O and Fe(NO3)3·9H2O are dissolved in water, and then isopropanol and ammonia water are added and stirred evenly, and then the solution is transferred to an autoclave for hydrothermal reaction. After the hydrothermal reaction, a CoFe@NBC precursor is obtained; 3) The CoFe@NBC precursor obtained in step 2) is placed in a tube furnace in a N2 atmosphere for calcination. After the calcination is completed, the material is taken out and ground after cooling to room temperature to obtain a CoFe@NBC composite catalyst.
2. The method for preparing a CoFe@NBC composite catalyst according to claim 1, characterized in that Step 1) The specific process of pre-treating the collected wheat straw is as follows: The collected wheat straw is repeatedly washed with water to remove dead leaves and dust on the surface, then placed in a drying oven at 105°C for 30 min, and then transferred to 60-80°C for drying. Finally, the dried wheat straw is crushed using a plant crusher to complete the pretreatment of the wheat straw biomass.
3. The method for preparing a CoFe@NBC composite catalyst according to claim 1, characterized in that Step 2) The mass ratio of wheat straw biomass powder to Co(NO3)2·6H2O and Fe(NO3)3·9H2O is 1:0.29-0.87:0.81-1.62; the mass fraction of ammonia water in the mixed solution is 44.69-51.86%.
4. The method for preparing a CoFe@NBC composite catalyst according to claim 1, characterized in that Step 2) The volume ratio of isopropanol to ammonia water is 1:0.71-2.
86.
5. The method for preparing a CoFe@NBC composite catalyst according to claim 1, characterized in that In step 2), the hydrothermal reaction temperature is 175-185°C and the reaction time is 12-13h.
6. The method for preparing a CoFe@NBC composite catalyst according to claim 1, characterized in that In step 3), the calcination temperature is 780-820°C and the calcination time is 3-4h.
7. A CoFe@NBC composite catalyst prepared by the method of claim 1.
8. Use of the CoFe@NBC composite catalyst according to claim 7 in activating peroxymonosulfate to degrade bisphenol S.
Citation Information
Patent Citations
Method for removing toxic organic pollutants in water through oxidation
CN117550705A
Biochar-loaded ferrocobalt alloy composite catalyst as well as preparation method and application thereof
CN117816169A
Cited By
Method for enhancing surface conductivity of biochar, composite material of biochar loaded with transition metal and application of composite material
CN119640303A
A method for enhancing the surface conductivity of biochar, a composite material of biochar loaded with transition metals, and applications thereof
CN119640303B
Oxygen-vacancy-enriched manganese dioxide magnetic carbon-based composite catalyst, preparation method thereof and application of composite catalyst in degrading bisphenol S by activating peroxymonosulfate
CN121198312A
Oxygen-rich vacancy manganese dioxide magnetic carbon-based composite catalyst, preparation method thereof and application thereof in activated peroxymonosulfate degradation of bisphenol s
CN121198312B